PENGGUNAAN MEDIA PERMAINAN KARTU KUARTET PADA PEMBELAJARAN MENULIS KARANGAN NARASI - Amin Syahputra (JURNAL SASTRA INDONESIA (SASINDO), 2012)
To be able to write, especially to write a narrative essay, students must first have an idea, the idea of ​​a skeleton events (conflict) at the same time and place the background. After that, then he can develop his idea into a narrative essay narrative intact. To that end, students need something that can be used as a source of inspiration or a source of ideas rather narrative. Temporal, cards quartet is four (quartet), each card contains a picture that explains the subtitle, while each card is linked to a subtitle headline. For example, the "Quartet" comprising the quartet cards headline "Berpariwisata", while each of the subheadings contained in a sequence of four cards is "Departure, Play, Home, and Accidents". On each card there is a picture that explains the subtitle of each. Thus, subtitled subtitled-card which is a series of events (in order) can be used as a source of ideas a narrative. Moreover, the image that explains each subtitle on the card can help to mengimasjinasikan setting the time and place in accordance with those events.   Keywords: Effect-Card quartet-narrative essay